Association of Menopause Related Vasomotor Symptoms with Socio-Demographic Factors - Nadia Jabeen,Saad Akmal,Salman Shabbir,Mahreen Mahmood (Journal of Rawalpindi Medical College, 2015)
Background : To find out the relationship of severity of menopause related vasomotor symptoms with socio-demographic factors. Methods: In this descriptive study 100 postmenopausal ladies with physiological menopause of ≥ 4 years and with vasomotor symptoms (hot flushes, night sweats) were included. All the women with premature menopause, surgical menopause, taking hormonal replacement therapy and with medical conditions like diabetes, hypertension, cardiac disease and thyroid disease were excluded. Severity of vasomotor menopausal symptoms was classified as, 0: None;1: Mild (Sensation of heat without sweating);2: Moderate (Sensation of heat with sweating able to continue activity);3: Severe (Sensation of heat with sweating causes cessation of activity).Association of vasomotor symptoms was assessed against educational status,professional status, socioeconomic status (monthly income) and body mass index (BMI).p value <0.05 was considered as statistically significant. Results: Mean age of women was 52 years while mean age of menopause was 49 years. All the participants were married. Vasomotor symptoms of mild severity were observed in women who were educated till matric, were doing job had family income >30,000, BMI between 25-27kg/m2. Severe vasomotor symptoms were observed in females who were uneducated or educated till primary, were housewives, had family income < 20,000 and BMI > 30kg/m2.A statistically significant relationship of vasomotor symptoms was found with socio-demographic factors (p<0.05). Conclusion: Socio-demographic factors have direct relationship with severity of vasomotor symptoms of menopause.